Daya Serap Hukum Islam di Indonesia pada Bidang Privat - Hatta, Akrama (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2017)
The adaptation of syari’ah law into the Indonesian national legal system has been one solution oﬀered to accomodate the tendency of moslem society in adopting the syari’ah law as a controlling system in various aspects of life specifcally the private. This eﬀort is applied by adopting syari’ah law and transforms it into national legal system through the constitution and regulation in many aspects. Within the process, the adopted syari’ah law in the national law aﬀects on many aspects signifcantly and is releavant with the plural society model. It shows that syari’ah law has the chance to be adopted within the national law aspects.